Single to multiple digital holograms for phase compensation and defect detection - Chen, Zhenkai; Zhou, Wenjing; Ge, Zhou; Yu, Yingjie; Zhang, Hongbo; Poon, Ting-Chung (Frontiers in Photonics, 2024)
Digital holography enables quantitative phase imaging based on interference. A digital hologram often encodes the phase information along with aberrations or deformations. This article reviews phase analysis and its diverse application solutions and challenges in digital holography including aberrations removal in a single hologram, defect and deformation detection using dual-holograms, and defect location in multi-holograms. The state-of-the-art of the techniques are presented and discussed in detail for phase analysis, separation, and quantification. Phase analysis in digital holography can provide high precision, high resolution, rapid quantitative and intelligent imaging abilities.